INTERIOR DESIGN OF CIVIL DEFENSE SHELTERS - Semyroz, Nina (Theory and practice of design, 2022)
The article is devoted to the study of the interior design of civil protection shelters, and is an attempt to draw the public’s attention to the means of creating acceptable conditions for the shelter of the civilian population. The purpose of the article is to analyze the main problems and difficulties that accompany the arrangement of such institutions, as well as to propose and systematize the main features and requirements that must be taken into account when developing design projects of civil defense shelter interiors. The research methodology consists in a systematic, comprehensive and comprehensive analysis of the problems of architectural design of the interiors of civil protection shelters. The research used the analysis of literary, normative, informational sources, grapho-analytical methods, photographs, and field research. The research methodology consists of a set of practical, theoretical, empirical, retrospective and factor analysis methods. The scientific novelty of the obtained results is that: – for the first time the factors were determined, the features were identified, the design principles of the interior arrangement of the shelter of the civil protection of the population were determined; – the methodology for the design of interiors of civil protection shelters has been improved; – the methods of forming the interior design of civil protection shelters gained further development. The practical significance of this article lies in the fact that it will be of interest to both researchers who study the interior design features of civil defense shelters, as well as users and builders.